Missing the boat: fatal ending to a missed case of Charcot arthropathy. (16th June 2020) - Galeazzi Rech, Anna Luiza; Stüve, Yvon; Toepfer, Andreas; Schimke, Katrin E
Abstract : Summary: Acute Charcot neuropathic osteoarthropathy (CN) is a clinical entity which can easily go unrecognized in its acute early stages due to lack of awareness and unspecific presentation. However, missing early diagnosis can lead to severe complications. We present the case of a 72-year-old male patient who went through the natural course of the disease unnoticed before the very eyes of his physicians leading to a tragic end. We aim to raise awareness for this rare diabetic complication, emphasizing the necessity of early diagnosis and adequate, interdisciplinary treatment. Learning points: Clinical signs and symptoms of acute Charcot neuropathic osteoarthropathy (CN). Red flags. Importance of early diagnosis and correct treatment. Diagnostic challenges of acute CN. Awareness of high morbidity and mortality.